Mini Group Discussion: Cooperative Learning in Teaching Reading - Maskhurin Fajarina; Sayid Ma’rifatulloh (Jurnal Ilmiah Wahana Pendidikan, 2020)
The aim of the research is to determine mini-group discussion as a cooperative learning in teaching reading. In the article, the method used is quantitative and descriptive qualitative which focus on teaching reading English text of Unhasy Students non-English department. It focus on some problems, those are How the implementation of mini group discussion (mindis) in teaching reading English and How the influence of (Mindis) into students’ ability in reading English comprehension. The researcher used test as an instrument and interview of the students. The result of the research are Mindis is easy to teach reading English in non-English department and it has significant influence into the students' ability in reading English.